In situ high-resolution structure of the baseplate antenna complex in Chlorobaculum tepidum - Jakob Toudahl Nielsen (Nature Portfolio, 2016)
The chlorosome of the photosynthetic bacterium C. tepidumharvests light and transfers the energy to the photosynthetic reaction centre. Here the authors determine the structure of the baseplate, a scaffolding super-structure, to show that the baseplate consists of rods of repeated CsmA dimers containing pigment molecules.